2017
DOI: 10.1016/j.jpain.2017.02.428
|View full text |Cite
|
Sign up to set email alerts
|

Feelings of Clinician-Patient Similarity and Trust Influence Pain: Evidence From Simulated Clinical Interactions

Abstract: Pain is influenced by many factors other than external sources of tissue damage. Among these, the clinician-patient relationship is particularly important for pain diagnosis and treatment. However, the effects of the clinician-patient relationship on pain remain under-examined. We tested the hypothesis that patients who believe they share core beliefs and values with their clinician will report less pain than patients who do not. We also measured feelings of perceived clinician-patient similarity and trust to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 62 publications
0
45
0
Order By: Relevance
“…In this light, medical encounters were interpersonal interactions and could represent dilemma situations, being interpreted as a possible source of conflicting interests between patients and doctors (Buchnam et al, 2016;Buchnam & Ho, 2013;Burgess et al, 2008;Chibnall et al, 2018;Dineen & Dubois, 2016;Kennedy et al, 2017;Matthias et al, 2013), such as when prescribing opioids in situations with 'potential for abuse' (Miller, 2007) or performing abortions in Brazil (Diniz et al, 2014). These ethical-interactive considerations of trust also included studies investigating relations between categories of identity (e.g., race, stigmatised conditions), trust and the delivery of care (Burgess et al, 2008;Losin et al, 2017;Moskowitz et al, 2011;Thom et al, 2011).…”
Section: Theoretical and Methodological Approachesmentioning
confidence: 99%
“…In this light, medical encounters were interpersonal interactions and could represent dilemma situations, being interpreted as a possible source of conflicting interests between patients and doctors (Buchnam et al, 2016;Buchnam & Ho, 2013;Burgess et al, 2008;Chibnall et al, 2018;Dineen & Dubois, 2016;Kennedy et al, 2017;Matthias et al, 2013), such as when prescribing opioids in situations with 'potential for abuse' (Miller, 2007) or performing abortions in Brazil (Diniz et al, 2014). These ethical-interactive considerations of trust also included studies investigating relations between categories of identity (e.g., race, stigmatised conditions), trust and the delivery of care (Burgess et al, 2008;Losin et al, 2017;Moskowitz et al, 2011;Thom et al, 2011).…”
Section: Theoretical and Methodological Approachesmentioning
confidence: 99%
“…In Losin et al 2017, we previously found that patients with concordant clinicians felt more trust and similarity toward their clinician, which in turn predicted lower pain ratings. 95 In the present study, we extend this work by investigating the role of motor synchrony between clinicians and patients, calculated from the recorded video of the interaction. We predicted that there would be lower pain ratings when patients were paired with concordant clinicians and that that effect would be mediated by their motor synchrony.…”
mentioning
confidence: 90%
“…Beyond an unnatural look, the three main concerns patient face are pain, complications, and procedural costs. 22 It is essential to discuss treatment costs, obtain financial consent, and plan over the long term to obviate financial stress. Addressing these issues upfront is instrumental in establishing the trust that underpins true patient satisfaction.…”
Section: Consentmentioning
confidence: 99%